The Use of Management Information System to Help Decision Making in Digital Firms - Alzhrani, Atyeh Mohammed (International Journal of Business and Management Future, 2020)
Management Information System (MIS) gives information for the managerial activities digital firms. This paper focuses on understanding the vital role of using management information system (MIS) in decision making in digital firms. It talks about considering the concept of MIS, the necessary use of MIS and the impact of the smart usage of MIS in decision making in digital firms. The study discusses MIS importance on decision making depending on a descriptive analytical method, in which the idea is discussed and described in an accurate methodology with analysis, through presenting and discussing previous studies, then relying on the comparative approach to know the role of using MIS in Digital organizations. The study revealed the effect of using MIS in decision making as a smart usage of MIS tool helps achieving a great success and minimizing the investigation of time in addition to increasing the profit of organizations. Also, it shows how decisions are made in digital firms using MIS and the challenges that the organizations facing in this process and a few recommendations to curb these challenges.